2019
DOI: 10.1111/os.12435
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Cervical Kinematic Quality Parameters in Planar Movement

Abstract: Comprehending cervical spinal motion underlies the understanding of the mechanisms of cervical disorders. We aimed to better define the clinical relevance of cervical spine kinematics, focusing on quality parameters describing cervical spine planar motion. The most common study focuses were kinematic quality parameters after cervical arthroplasty and in normal subjects, patients with cervical degeneration, and patients with cervical deformities. Kinematic quality parameters are important for cervical degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…After ACDA, emphasis is often placed on presence and magnitude of motion as assessed by ROM, while quality of motion by parameters like instantaneous COR, COR, and instantaneous axis of rotation has just recently been identified as important for evaluating changes in the cervical motion pattern. 40 - 43 Anderst et al demonstrated that the instantaneous COR was generally fixed in the longitudinal direction, but it translated in the anterior-posterior direction during flexion-extension. 42 If translation is not adequately possible, non-physiologic stress on the facet joints at the index level ensues, which may cause facet joint syndrome, as it has commonly been seen in lumbar disc arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After ACDA, emphasis is often placed on presence and magnitude of motion as assessed by ROM, while quality of motion by parameters like instantaneous COR, COR, and instantaneous axis of rotation has just recently been identified as important for evaluating changes in the cervical motion pattern. 40 - 43 Anderst et al demonstrated that the instantaneous COR was generally fixed in the longitudinal direction, but it translated in the anterior-posterior direction during flexion-extension. 42 If translation is not adequately possible, non-physiologic stress on the facet joints at the index level ensues, which may cause facet joint syndrome, as it has commonly been seen in lumbar disc arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“… 44 It has been postulated that these further findings should be considered in clinical practice and when designing disc prostheses. 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is known as perpendicular bisector method. [19][20][21] COR was measured in millimeters (mm). The COR coordinates were measured and standardized by dividing the length, width, and height of the upper vertebrae to eliminate individual differences.…”
Section: Calculation Of the Lumbar Center Of Rotationmentioning
confidence: 99%
“…Due to the lack of a simple and effective method to evaluate three-dimensional cervical motion, cervical kinematics studies are mainly based on sagittal flexionextension motion [7]. The center of rotation (COR) is the sagittal motion center of the functional spinal unit (FSU) measured using cervical flexion-extension radiographs [7,8]. COR is relatively simple to measure and can be readily subjected to statistical analysis and comparison.…”
Section: Introductionmentioning
confidence: 99%